2021
DOI: 10.24953/turkjped.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut microbiota is associated with feeding intolerance in preterm infants

Abstract: Background. Feeding intolerance (FI) is a common complication that may cause great harm to preterm infants. The mechanism of FI remains unclear, but probiotics may help prevent and alleviate its symptoms. We hypothesized that the alteration in gut microbiota may be associated with the development of FI. Our study aimed to investigate the association between gut microbiota and FI in preterm infants. Methods. Ninety-seven preterm infants were divided into the FI group (N=42) and the feeding tolerance (FT) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Altered gut microbiome have been implicated in the progressions of FI. Several studies have explored the microbial alterations in preterm infants with FI, revealing reduced diversity, changes in microbial distribution, and an increased relative abundance of the Proteobacteria phylum and Klebsiella genus [11][12][13][14][15]. However, due to variations in study populations, sampling time points, and sampling frequency, definitive conclusions have not yet been reached.…”
Section: Introductionmentioning
confidence: 99%
“…Altered gut microbiome have been implicated in the progressions of FI. Several studies have explored the microbial alterations in preterm infants with FI, revealing reduced diversity, changes in microbial distribution, and an increased relative abundance of the Proteobacteria phylum and Klebsiella genus [11][12][13][14][15]. However, due to variations in study populations, sampling time points, and sampling frequency, definitive conclusions have not yet been reached.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, we found that most preterm infants would benefit from increased enteral feeding amounts as expected, but the reduction in risk of SHCG was not as impactful as microbiome supplantation, and further, there was a smaller subset of infants for which increasing enteral feeding amounts would greatly increase the risk of SHCG. Feeding intolerance of preterm infants has been linked to dysbiosis of the gut microbiome ( 74 , 75 ), and certain randomized controlled trials of probiotic administration to preterm infants in the NICU demonstrate decreased incidences of feeding intolerance ( 76 78 ). Therefore, our methodology is additionally able to resolve when non–microbiome-based interventions may be more appropriate, and also when such interventions would likely be inappropriate given the underlying microbiome structure of the infant such as ramping up enteral feeds.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the microbiome on compensatory growth or extrauterine growth restriction (EUGR) was not included because the weight of most of the SGA infants was still below the 10th percentile at the time of discharge. Feeding, weight gain, and catch-up growth are related to microbial community structure [ 10 , 22 , 52 , 53 , 54 , 55 ]. In a rat model, the decrease in the abundance of Lactobacillus was significantly associated with catch-up growth [ 10 ].…”
Section: Discussionmentioning
confidence: 99%